PROFITS: A CASE OF EXCHANGE RATE VOLATILITY - Budiono, Gatut L; Firdayasa, Agnesya (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The purpose of this research was to measure the effect of exchange rate volatility on the companiesÃ¢â‚¬â„¢ profit in food and beverages sub sector with revenue and expenses as an intervening. The analysis technique used in this research was regression and path analysis.Ã‚Â The financial statement and middle exchange rate of first quarter of 2012 to 2015 third quarter IDX and BI secondary data was incorporated in the research. These research result showed that the exchange rate volatility may affect companiesÃ¢â‚¬â„¢ profit in food and beverages sub sector either directly or indirectly.